The Chinese Herbal Medicine Formula Sheng-Fei-Yu-Chuan-Tang Suppresses Th2 Responses and Increases IFNγ in Dermatophagoides pteronyssinus Induced Chronic Asthmatic Mice. (14th March 2013) - Lin, Chia-Hung; Yeh, Ching-Hua; Lin, Li-Jen; Wang, Jen-Shu; Wang, Shulhn-Der; Kao, Shung-Te
Abstract : Sheng-Fei-Yu-Chuan-Tang (SFYCT), a traditional Chinese medicine formula consisting of 13 medicinal plants, has been used in the treatment of asthma. This study demonstrated the immunoregulatory effect of SFYCT on chronic allergic asthma using the Dermatophagoides-pteronyssinus- (Der p-) challenged chronic asthmatic murine model. SFYCT decreased the airway hyperresponseness (AHR), pulmonary inflammatory cell infiltration, and airway remodeling in Der p mice. SFYCT treatment decreased Der p-induced total IgE and Der-p-specific IgG1 but not IgG2a/2b Ab titer in serum of Der p mice. SFYCT also decreased Th2 cytokines, IL-4, IL-5, and IL-13, but increased IFN- γ and IL-12 in the BALF of Der p mice. TGF- β 1 and collagen production in the lung of mice were decreased by SFYCT. The mRNA expression of chemokine including Eotaxin, RANTES, and MCP-1 in the lung of Der p mice was decreased by SFYCT. In conclusion, the suppressed Der-p-induced airway inflammation, remodeling, and hyperresponseness in chronic asthma murine model are related to SFYCT inhibits Th2 responses, decreases chemokine expression and promotes IFN- γ and IL-12 production. SFYCT could show Der-p-induced Th2 responses to Th1 responses by increasing IFN- γ which is merit for clinical application on asthma patients.